(untitled) (Canadian Medical Education Journal, 2012)
Background: There has been a steady erosion of family physicians with enhanced surgical skills providing care for rural residents. This has been largely due to the lack of formal training avenues and continuing medical education (CME) opportunities afforded to those interested and attrition of those currently practicing.. Methods: A qualitative study was undertaken using an exploratory policy framework to guide the collection of in-depth interview data on GP surgeons’ training experiences. A purposive sample of GP surgeons currently practicing in rural BC and Alberta communities yielded interviews with 62 participants in person and an additional 8 by telephone. Interviews were audio recorded and transcribed then subjected to a process analysis. Results: Participants thematically identified motivations for acquiring advanced skills training, resources required (primarily in the area of solid mentorship), the most efficacious context for a training program (structured) and differences in mentorship between obstetricians and general surgeons. Conclusions: Mentors and role models were the most salient influencing factor in the trajectory of training for the participants in this study. Mentorship between specialists and generalists was constrained at times by inter-professional tensions and was accomplished more successfully within a cirriculum-based, structured environment as opposed to a learner-responsive training environment.